2011
DOI: 10.1177/1352458511408475
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the 2- and 6-minute walk test in multiple sclerosis

Abstract: The 6-minute walk test (6MWT) is often used to assess walking distance in multiple sclerosis (MS), but can be both time consuming for the investigator and exhausting for people with MS (pwMS). The present report compared the 6MWT scores of 40 ambulatory pwMS with their scores on the shorter 2-minute walk test (2MWT). The 2MWT estimated the 6MWT results with a mean relative error of 5% (R(2) = 0.96; p < 0.01). As the last 4-minute period of the 6MWT seems redundant, the 2MWT may be considered as a practical rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
129
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(140 citation statements)
references
References 10 publications
10
129
1
Order By: Relevance
“…This finding is supported by other studies that have found reduced speed in the last one to five minutes of the 6MWT in people with MS [35,36]. Gait slowing appears to coincide with steady state aerobic metabolism, as Motl et al demonstrated with physiological measurements during the final three minutes of the 6MWT [37].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This finding is supported by other studies that have found reduced speed in the last one to five minutes of the 6MWT in people with MS [35,36]. Gait slowing appears to coincide with steady state aerobic metabolism, as Motl et al demonstrated with physiological measurements during the final three minutes of the 6MWT [37].…”
Section: Discussionsupporting
confidence: 79%
“…A 'deceleration index' may be a useful measure of walking behaviour in MS [7], as a recent study showed 'decline' in walking speed , rather than 'mean' walking speed over the 6MWT to have a stronger association with self-reported fatigue [34]. While there has been some support for a shortened two-minute walk test to assess walking ability in people with MS [36], our findings suggests six minutes may be required to gain important clinical information on walkinginduced fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…The reliability of the 2-minute Walk Test (2mWT) has not been reported, although it is assumed to be high based on its strong correlation with the first 2 min of the 6-minute Walk Test (6mWT). 19 …”
Section: Reliabilitymentioning
confidence: 99%
“…In subjects with lower limb amputations, the distance walked is well correlated with daily activity and indicative for substantial functional limitations in daily life [33,34].Timed walk tests have not yet been validated specifically for users of KAFOs, but for patients with neurologic conditions that may require fitting of a KAFO such as incomplete SCI, stroke, traumatic brain injury, or multiple sclerosis [35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%